2019
DOI: 10.1021/acscatal.9b04204
|View full text |Cite
|
Sign up to set email alerts
|

N,C-Disubstituted Biarylpalladacycles as Precatalysts for ppm Pd-Catalyzed Cross Couplings in Water under Mild Conditions

Abstract: Various monosubstitution and disubstitution patterns on the parent biarylamine skeleton characteristic of palladacycles, as well as the counterion effect, have been studied while looking for ways to increase the effectiveness of the catalyst formed under micellar catalysis conditions in water, with the goal of reducing the amount of Pd needed for coupling reactions. Several substituted palladacycles containing readily accessible ligands were chosen for evaluation. The results indicate that (1) preactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…11d) was also developed for Suzuki-Miyaura, Heck, and Sonogashira couplings that involve 1500-3000 ppm (0.15-0.30 mol%) levels of this Pd catalyst. 40 Beyond the hydrophobic effect, another feature worthy of note regarding the newly inserted isopropyl groups was also observed in the case of the same palladacycle. The N-isopropylcarbazole, formed from in situ decomposition of the palladacycle, competes less effectively for ligation of palladium.…”
Section: (D) Solvent Isotope Effectmentioning
confidence: 86%
See 1 more Smart Citation
“…11d) was also developed for Suzuki-Miyaura, Heck, and Sonogashira couplings that involve 1500-3000 ppm (0.15-0.30 mol%) levels of this Pd catalyst. 40 Beyond the hydrophobic effect, another feature worthy of note regarding the newly inserted isopropyl groups was also observed in the case of the same palladacycle. The N-isopropylcarbazole, formed from in situ decomposition of the palladacycle, competes less effectively for ligation of palladium.…”
Section: (D) Solvent Isotope Effectmentioning
confidence: 86%
“…Direct comparison between N-isopropyl, N-methyl, and N-H carbazoles showed that the presence of the N-isopropyl group had little impact on the level of conversion, while both the Nmethyl and N-H carbazoles clearly inhibit the coupling reaction to a greater extent (Table 4). 40 Similar aqueous micellar conditions have been used to form C-N bonds via amination reactions where a p-allylpalladium precursor was found to be the most effective catalyst. The allylic moiety initially on palladium and bearing the more lipophilic substituent (i.e., phenyl > methyl > hydrogen) led to the most successful coupling (Fig.…”
Section: (D) Solvent Isotope Effectmentioning
confidence: 99%
“…Recently, however, it has been shown that the carbazole by‐product resulting from base‐induced decomposition of the palladacycle pre‐catalyst can impact cross‐coupling reactions, presumably by competitive ligation of nitrogen to palladium [16] . To minimize such ligation, which could be playing a critical role in these couplings given the ppm level of Pd, the corresponding N ‐alkylated analogues were prepared ( P8 and P9 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, triphenylphosphine is known be a good choice for enhancing transmetallation of organostannanes [14] while being a far less costly item of commerce. We have recently disclosed processes based on substituted biarylamine‐containing palladacycles, that together with our newly designed ligands allow for ppm level catalyst loadings for use in Suzuki–Miyaura [15] and Mizoroki–Heck cross‐coupling reactions in water [16] . In efforts to develop even more cost‐effective and sustainable processes for use in organic synthesis, [17] we have prepared a new PPh 3 ‐based palladacycle from commercially available and inexpensive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous Suzuki-Miyaura cross-coupling reactions are particularly promising due to the water tolerance of boronic acids compared with the organometallic reagents required for other cross-coupling protocols. As a consequence, the Suzuki-Miyaura reaction has been widely developed under homogenous or heterogenous catalytic conditions in water media and a large array of different ligands and palladium complexes including micellar catalysis conditions nanoparticulate formulations have been designed to increase efficiency under aqueous conditions [6][7][8][9][10][11][12][13][14][15][16]. The water and functional group tolerance of the Suzuki-Miyaura reaction culminated in the cross-coupling of iodoarylated proteins under physiological conditions opening the way to a realm of chemical-biology applications [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%